Regional Structural Orientation of the Mount Sharp Group Revealed by In Situ Dip Measurements and Stratigraphic Correlations on the Vera Rubin Ridge. Issue 5 (5th May 2020) - Stein, Nathaniel T.; Quinn, Daven P.; Grotzinger, John P.; Fedo, Christopher; Ehlmann, Bethany L.; Stack, Kathryn M.; Edgar, Lauren A.; Fraeman, Abigail A.; Deen, Robert
Abstract: Ground‐based bedding orientation measurements are critical to determine the geologic history and processes of sedimentation in Gale crater, Mars. We constrain the dip of lacustrine strata of the Blunts Point, Pettegrove Point, and Jura members of the Murray formation using a combination of regional stratigraphic correlations and bed attitude measurements from stereo Mastcam images taken by the Mars Science Laboratory Curiosity rover. In situ bed attitude measurements using a principal component analysis‐based regression method reveal a wide range of dips and dip azimuths owing to a combination of high stereo errors, postdepositional deformation of strata (e.g., fracturing, rotation, and impact cratering), and different primary depositional dips. These constrain regional dips to be within several degrees of horizontal on average. Stratigraphic correlations between targets observed in the Glen Torridon trough and at the Pettegrove Point‐Jura member contact of Vera Rubin ridge (VRR) constrain dips to be between 3°SE and 2°NW, consistent with nearly flat strata deposited horizontally on an equipotential surface. The Jura member is determined to be stratigraphically equivalent to the northern portion of the Glen Torridon trough. Rover‐based dip magnitudes are generally significantly shallower than the orientation of VRR member contacts measured from High Resolution Imaging Science Experiment‐based traces, suggesting the sedimentary strata and VRR member contacts may be discordant. Plain Language Summary: The orientation of sedimentary strata is one of the most fundamental measurements of structural geology because it records information about the processes of deposition and subsequent deformation of those strata. For the last 7 years, the Curiosity rover has traversed predominantly fluviolacustrine (river‐ and lake‐deposited) strata. Recently, the rover traversed the Vera Rubin ridge (VRR), a topographic rise within a larger collection of strata with rock exposures whose orientation can be measured using overlapping (stereo) images taken by cameras aboard the rover. By measuring the orientation of beds in stereo rover images and comparing the elevation of similar rock lithologies found along the traverse, we constrain the strata that comprise the VRR to be horizontal or only shallowly dipping. This result is consistent with the sediment that formed the VRR being deposited on a nearly horizontal surface, suggesting that at least the strata that make up the lower portion of Mount Sharp, the large sedimentary mound in Gale crater that dips more steeply outward, may not have directly contributed to its primary formation. The near‐flat orientation also indicates that some portion of the VRR occurs at the same elevation as the region south of the ridge called Glen Torridon. Key Points: We use stereo rover images and stratigraphic correlations to constrain the dip of Vera Rubin ridge strata to be flat or nearly flat The Jura member of the Vera Rubin ridge is stratigraphically equivalent to part of Glen Torridon Vera Rubin ridge member contacts and the strata that comprise them are likely discordant